Electrophysiological studies in cerebrotendinous xanthomatosis. - Tokimura, Y (1992)
Seven patients with cerebrotendinous xanthomatosis (CTX) were studied by electrophysiological techniques. The percentages of abnormalities detected in nerve conduction studies and electroencephalograms were 28.6% (two patients) and 100%, respectively. All patients showed prolonged central conduction times in short latency somatosensory evoked potentials (SSEPs) by tibial nerve stimulation but normal SSEPs by median nerve stimulation. Brain stem auditory evoked potentials and visual evoked potentials were abnormal in three (42.9%) and four patients (57.1%), respectively. These electrophysiological parameters were correlated with the ratio of serum cholestanol to cholesterol concentration. The results of SSEPs suggest that the polyneuropathy in CTX is caused by distal axonopathy affecting longer axons before shorter axons (central-peripheral distal axonopathy).